Performance of GPR Influenced by Electrical Conductivity and Dielectric Constant. (2016) - Alsharahi, Gamil; Driouach, Abdellah; Faize, Ahmed
Abstract: The geological radar or GPR (Ground Penetrating Radar) is an electromagnetic system used in non-destructive investigations of subsoil. It is based on the emission by an antenna coupled to the ground, of short electromagnetic pulses of harmonic waves sweeping a certain frequency band. We discuss in this work, the simulation of radar signals GPR, using Reflexw. Note, however, that the operation of this program is based on numerical methods including finite difference method time domain (FDTD) for this software. The simulations we have performed include the following items: an iron bar, a plastic tube and a plastic water bottle. Have led us to find that the electromagnetic waves are very sensitive to variations in the dielectric permittivity and electrical conductivity.